(3GdEYdGe ChdG (B/s ((3dHfGf (B:s (3OGQ GdfaGFS ddfTQ hGdJhRjY ,s, 1994)
(3jWQM GdeDda h gh HMGKI eJNUU aj GdOQGSGJ GdESdGejI h GdacQjI aj gPG GdcJGH CacGQG h YfGUQg hhSGFdg h jHjf eG jLH Gf jJMdi Hg QLd GdEYdGe GdYQHj GdeSde aj GdeQMdI GdbGOeI dcj dG JJcQQ GdeCSj GdJj NdagG GdEdGe GdZHj h GdEYdGe GdVYja (B.(3Efg cJGH jVY GddHfGJ GdGhdi aj NWI GdYQHj GdeSde edJRe HbVGjG GdCeI h eHGOFgG HcTa GdZWGA Yf CNWGA GdeGVj dJchf YHQI dEYdGe GdeSJbHds
Keywords: (3GdEYdGes; (3GdNHQ GdUMajs; (3GdUMGaIs